2009
DOI: 10.1097/scs.0b013e3181ae4139
|View full text |Cite
|
Sign up to set email alerts
|

Airway Analysis

Abstract: Mandibular distraction is effective at relieving anatomic airway obstruction in infants with micrognathia and obstructive sleep apnea while avoiding some previously reported associated complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…PRS infants who have undergone MDO have shown clinical improvement and significant increases in distance from pharyngeal wall to tongue base, cross sectional airway and hypopharyngeal airway volumes on CT (102, 103). A published meta-analysis has shown that MDO is effective in preventing tracheostomies in 91.3% of infants, and in relieving symptoms of OSA in 97% of the affected children (104).…”
Section: Treatment Of Osa In Children With Pierre Robin Sequencementioning
confidence: 99%
“…PRS infants who have undergone MDO have shown clinical improvement and significant increases in distance from pharyngeal wall to tongue base, cross sectional airway and hypopharyngeal airway volumes on CT (102, 103). A published meta-analysis has shown that MDO is effective in preventing tracheostomies in 91.3% of infants, and in relieving symptoms of OSA in 97% of the affected children (104).…”
Section: Treatment Of Osa In Children With Pierre Robin Sequencementioning
confidence: 99%
“…Twelve articles fulfilled the 5 criteria and entered the final round of critical appraisal. [ 45 , 64 , 75 , 77 , 79 , 85 , 87 , 95 , 96 , 100 , 101 , 124 ] All the 12 articles passed the appraisal and were included in the final review. The study selection process was shown in flow diagram in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies mentioned the need for postoperative monitoring or delayed extubation in the intensive care unit for several days (1–11.4 days) until the postsurgical swelling subsided or until the desired amount of distraction was achieved. [ 64 , 75 , 77 , 79 , 87 , 101 , 124 ] The mean reported follow-up period ranged from 6 to 37 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of osseous elements hypoplasia and deformity, the facial abnormal growth potential of the affected and adjacent skeleton, the soft tissue, and nervous system impairment are factors that need taking into consideration 14 . MDO is an excellent assist to address the above concerns very well 8,16,17 . MDO not only lengthens the affected skeleton but also extends the associated soft-tissue envelope, therefore, improving the airway and facial appearance of patients 1,8 .…”
Section: Discussionmentioning
confidence: 99%